Effect of sonic and ultrasonic activation on physicochemical properties of root canal sealers (Journal of Applied Oral Science, 2022)
Objective: To evaluate the effect of ultrasonic and sonic activation on physicochemical properties of AH Plus, MTA Fillapex, ADSeal, GuttaFlow Bioseal, and GuttaFlow 2 sealers. Methodology: Three experimental groups were formed: no activation (NA), ultrasonic activation (UA), and sonic activation (SA). The sealers were manipulated according to the manufacturers’ instructions. A 3-mL syringe was adapted to receive 1 mL of sealer. Activation was performed with a 20/.01 ultrasonic insert (20 s/1W) in the UA group. A size 35.04 sonic tip was used (20 s/10,000 cycles/min-1) in the SA group. The molds for physicochemical analysis were filled and evaluated according to ANSI/ADA specification no. 57: setting time (ST), flow (FL), dimensional change (DC), solubility (SB), and radiopacity (RD). Statistical analysis was performed by Kruskal-Wallis, one-way ANOVA, and Tukey's tests (P<0.05). Results: Regarding ST, only AH Plus and GuttaFlow 2 in the NA group met the ANSI/ADA standards. All FL values were greater than 20 mm in diameter, as determined by ANSI/ADA. The tested sealers and protocols did not comply with the ANSI/ADA standards for DC. As for SB, only MTA Fillapex, regardless of the activation protocol, did not follow the ANSI/ADA standards. All of the investigated sealers, regardless of the activation protocol, presented radiographic density higher than 3 mm Al, as proposed by ANSI/ADA. Conclusions: UA and SA promoted changes in the physicochemical properties of the evaluated root canal sealers, mainly in ST and F. Thus, it is important to evaluate the physicochemical properties of endodontic sealers associated with activation techniques prior to clinical application in order to determine whether the properties follow the parameters set by ANSI/ADA, ensuring safety and quality of root canal filling.